2022
DOI: 10.3389/fgene.2022.932073
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Aarskog-scott syndrome caused by FGD1 gene variation: A family study

Abstract: Aarskog-Scott syndrome is a rare genetic disorder characterized by short stature, abnormal facial features, and digital and genital deformities. FGD1 gene variation is the known cause of this disorder. This paper described a Chinese family study of Aarskog-Scott syndrome in which the main patients were two brothers. Then, the relationship between genotype and phenotype in Aarskog-Scott syndrome was investigated preliminarily. A new FGD1 gene variant was revealed in this study, providing insights into the link … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…However, the available data were still limited. There were only three FGD1 -related AAS patients reported to receive rhGH treatment, with two patients having improved height [ 18 – 20 ]. In our study, rhGH treatment showed height improvement in the patients, and there were no serious adverse reactions during the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the available data were still limited. There were only three FGD1 -related AAS patients reported to receive rhGH treatment, with two patients having improved height [ 18 – 20 ]. In our study, rhGH treatment showed height improvement in the patients, and there were no serious adverse reactions during the treatment.…”
Section: Discussionmentioning
confidence: 99%